MORPHOMETRIC ANALYSIS OF MAXILLARY TUBERCLES IN CHILDREN TO DENERMINE THE POSSIBILITY OF THEIR USE AS A SUPPORT FOR DISTALIZATION - Zaiats, O.R.; Ozhogan, Z.R.; Ozhogan, I.A. (World of Medicine and Biology, 2020)
High intensity and prevalence of carious process lead to premature extraction of deciduous teeth and the creation of favorable conditions for development of anomalies and deformities. To improve the efficacy in treatment of dentoalveolar malocclusions which occur as a result of pathological mesial displacement of the maxillary lateral teeth, we considered the possibility of using the maxillary tubercles as a self-sustained or additional distal support to move the permanent molar in the distal direction. As a result of studying the features of the maxillary tubercles structure, we proposed their distribution according to their form: a) flat; b) sloping; c) convex; by height into: a) low (up to 2 mm); b) medium (2-3 mm); c) high (more than 3 mm); by length into: a) short (up to 5 mm); b) medium (5-8 mm); c) long (more than 8 mm). The prevalence of maxillary tubercles different in sizes and shapes in children of different age groups was studied, as well as the orthodontic apparatus for molars distalization using a high convex maxillary tubercle as a distal support.
Keywords: children; maxillary tubercles; pathological mesial displacement of the first permanent molars; anchor system; molars distalization